Manufacturing of Screw Rotors Via 5-axis Double-Flank CNC Machining. (March 2021) - Bizzarri, Michal; Bartoň, Michael
Abstract: We investigate a recently introduced methodology for 5-axis flank computer numerically controlled (CNC) machining, called double-flank milling (Bo et al., 2020). We show that screw rotors are well suited for this manufacturing approach where the milling tool possesses tangential contact with the material block on two sides, yielding a more efficient variant of traditional flank milling. While the tool's motion is determined as a helical motion, the shape of the tool and its orientation with respect to the helical axis are unknowns in our optimization-based approach. We demonstrate our approach on several rotor benchmark examples where the pairs of envelopes of a custom-shaped tool meet high machining accuracy. Graphical abstract: Highlights: The method for 5-axis double-flank CNC machining of screw rotor sis presented. The shape of the milling tool is an unknown in our optimization-based framework. For symmetric profiles, there exists a custom-shaped tool that is provably exact. For non-symmetric profiles, our approximation results meet fine machining tolerances. We validate our approach on several screw rotor benchmarks.